Pedagogicalization of Society and the Crisis of Education. Elements for a Criticism of Criticism(s) - Carlos Ernesto Noguera-Ramírez; Gustavo Adolfo Parra León (Universidad Pedagógica Nacional, 2016)
This text analyzes the circumstances under which critical thinking arises. Starting from them, the study makes a criticism to critical perspectives, given their key role in education and pedagogy. For this purpose, the authors take Foucault's genealogy of criticism in modern thinking, as well as his developments in relation to governmentability, and focuses in the analysis of current notions of freedom, interest and individual rights as conditions of what we might call the present impasse of education. That is to say, the freezing or impossibility to teach in contemporary societies.